PENGARUH KOMPETENSI TUTOR, HARGA DAN PRESTASI BELAJAR SISWA TERHADAP LOYALITAS PELANGGAN LEMBAGA BIMBINGAN BELAJAR DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Anastasia Sofie Widyastuti; Sutrisno Sutrisno (STIE Wiyatamandala, 2020)
Education is an important factor in the development and progress of a nation. The development of the current education sector is marked by the many businesses that are engaged in the field of educational support services (Private Tutoring Institutions). This study aims to find out how the influence of tutor competency, course price level and learning achievement on customer loyalty through satisfaction in the Private Tutoring Institution “Master Privat”. The object of the study was the students and parents of Master Private’ students as many as 100 respondents. The method of collecting data is by distributing questionnaires. Then the data is analyzed using Path Analysis techniques with software Lisrel version 8.80 and SPSS version 22. The results showed that tutors' competency, price and learning achievement, each had a partial and significant direct effect on satisfaction. Tutor competency, price and learning achievement have a simultaneous effect on satisfaction. And the final result is the competence of the tutor, price and learning achievement influence on customer loyalty through satisfaction as an intervening variable